Squid industry by-product hydrolysate supplementation enhances growth performance of Penaeus monodon fed plant protein-based diets without fish meal - Pan, Maila V.; Cadiz, Rowena E.; Mameloco, Emelyn Joy G.; Traifalgar, Rex Ferdinand M. (Frontiers in Sustainable Food Systems, 2022)
The poor growth of aquatic animals fed with diets containing high plant proteins has been attributed to low diet acceptability and feed value. Supplementation of protein hydrolysate, with high contents of free amino acids and soluble low molecular weight peptides, may increase the acceptability and feed value of a plant protein-based diet. In the present work, squid processing by-products were enzymatically hydrolyzed and used as a supplement in a plant protein-based diet, without fish meal, of Penaeus monodon to fully maximize the utilization of this marine resource. The hydrolysate was incorporated at 0, 0.5, and 1% levels in P. monodon diets containing 0 and 10% fish meal levels. Growth, digestive enzyme activities, muscle growth-, gut pro-inflammatory and immune-related gene expressions, and muscle morphometric measurements were evaluated as biological indices in an 8-week feeding trial. The squid by-product hydrolysate produced in the present study contains 90.25% protein, 5.84% lipid, and 3.91% ash, and has a molecular weight of 3.76 kDa. Supplementation at 1% hydrolysate in the experimental shrimp diet without fish meal resulted in the highest growth performance associated with increased feed intake, efficient feed and nutrient conversion and retention, enhanced digestive enzyme activities, upregulation of muscle growth- and immune-related genes, and suppression of the gut pro-inflammatory gene. The growth promotion is also linked with a significant increase in muscle mean fiber area, which suggests hypertrophic growth in shrimp. Generally, the supplementation of 1% squid by-product hydrolysate supported the growth of P. monodon fed on a plant protein-based diet without fish meal.